Consumer Expenditures and the Faith Factor - Showers, Vince E. (Interdisciplinary journal of research on religion, 2014)
This study examines the relationship between religious giving (an accessible behavioral indicant of religious commitment or religiosity) and expenditure patterns in the United States. Using a log- normal double-hurdle model adjusted for heteroscedasticity to estimate both the likelihood of participating in a purchase and the amount of a participant's expenditures provides evidence of significant differences from the impact of religious giving on expenditure categories predicted by scripture. These include spending in moderation on housing and managing risk with insurance and healthy living (lower tobacco and alcohol consumption). Region was also found to delineate differences in the impact of religiosity on expenditure patterns. Results of this study support the hypothesis that religious givers are indeed making conscious expenditure allocation choices requiring a rational choice and that many of those choices are consistent with Judeo-Christian or biblical principles.